Regulatory Roles of Long Non-Coding RNAs in the Central Nervous System and Associated Neurodegenerative Diseases - Quan, Zhenzhen; Zheng, Da; Qing, Hong (Frontiers in Cellular Neuroscience, 2017)
Accumulating studies have revealed that the human genome encodes tens of thousands of long non-coding RNAs (lncRNAs), which participate in multiple biological networks modulating gene expression via transcriptional, post-transcriptional and epigenetic regulation. Strikingly, a large fraction of tissue-specific lncRNAs are expressed in the Central Nervous System (CNS) with precisely regulated temporal and spatial expression patterns. These brain-specific lncRNAs are also featured with the cell-type specificity, the highest signals of evolutionary conservation, and their preferential location adjacent to brain-expressed protein-coding genes. Mounting evidence has indicated dysregulation or mutations in lncRNA gene loci are associated with a variety of CNS-associated neurodegenerative disorders, such as Alzheimer’s, Parkinson’s, Huntington’s diseases, Amyotrophic Lateral Sclerosis and others. However, how lncRNAs contribute to these disorders remains to be further explored and studied. In this review, we systematically and comprehensively summarize the current studies of lncRNAs, demonstrate the specificity of lncRNAs expressed in the brain, their functions during neural development and expression profiles in major cell types of the CNS, highlight the regulatory mechanisms of several studied lncRNAs that may play essential roles in the pathophysiology of neurodegenerative diseases, and discuss the current challenges and future perspectives of lncRNA studies involved in neurodegenerative and other diseases.